Multi-Party Model in Cooperatives : Deep Understanding of Ratio Legis in Minister of Cooperatives Regulation Number 8 of 2021 - Awaliya, Monica; Sukarmi, Sukarmi; Sihabudin, Sihabudin (IJBLE Scientific Publications Community Inc., 2024)
In line with the progress of the global economy, especially in Indonesia, it is recognized that a digitalization and modernization era has taken place, which continues to evolve and never ceases. This necessitates cooperatives to strengthen themselves to be healthier, self-reliant, modern, strong, and competitive, in accordance with cooperative principles, enabling them to play a role as a